Renal cell carcinoma in Nigeria: A systematic review - Akinfenwa Taoheed Atanda (Sahel Medical Journal, 2017)
Literature on renal cell carcinoma (RCC) in Nigeria is characterized by lacunae in several important areas with resultant incomprehensiveness of data. This requires a review of the literature so as to streamline the data. Using internet search engines, data were extracted from a total of twelve studies reported in peer reviewed journals between 2000 and 2015 from various states of Nigeria including Kano. These were subsequently collated, analyzed, and then compared with those from other parts of the world. There is relatively low incidence rate of 0.3/100,000 population; slight male preponderance and affectation of younger age groups with average age at diagnosis of 45 ± 4 years. Significant smoking history, exposure to industrial dye, family history, and HIV associated immunodeficiency are major risk factors of RCC in Nigeria. A significant number of cases presented with triad of loin pain, hematuria, and loin mass; advanced disease and bulky tumors of up to 3.8 kg and 56 cm. The predominant histological subtypes were clear cell carcinoma 60%–85.7% and papillary carcinoma 23.8%–46.2%. In general, there has been poor overall outcome for RCC bearing patients in the country. RCC in Nigeria is characterized by earlier age at onset and poor outcome, thus necessitating more aggressive case identification at early stages so as to improve prognosis.